Gestión de bienes muebles en instituciones educativas y control patrimonial en la Unidad de Gestión Educativa Local Bolívar: Provincia Bolívar, Región La Libertad, años 2016-2017 - Pajuelo Chavarry, Johane Sarai (2017)
The present investigation is based on the province of Bolívar, La Libertad Region, Peru. Its main objective is to determine the relationship between the Management of Furniture Goods in educational institutions and the Patrimonial Control of the Bolivar Local Education Management Unit, Provincia Bolívar, Region La Libertad, from 2016 to 2017. After analyzing the problematic reality, the research problem was formulated: What is the relationship between the Management of Furniture Goods in educational institutions and the Patrimonial Control in the Local Educational Management Unit of Bolivar; Province Bolivar, Region La Libertad, years 2016 - 2017?. In the collection of data, two populations were taken into account: 79 directors of educational institutions and 15 workers in the Logistics area of the UGEL; the sample being the same as the population; to whom a survey was applied. From the results obtained, the corresponding discussion has been carried out, demonstrating the validity of the hypothesis: "The Management of Furniture Goods in educational institutions have a positive and significant relationship with the Patrimonial Control of the Local Educational Management Unit of Bolivar; Province of Bolívar, La Libertad Region, 2016 - 2017 ". The main recommendation is that the quantitative relationship between Asset Management and Asset Control is moderate and significant, according to the Pearson correlation coefficient applied to the workers (r = 0.688) as well as to directors (r = 0.612) and qualitative way the relationship between variables is close with only a difference of 1.21 points. Therefore, it is recommended to carry out periodic investigations on the processes of Furniture Property Management to detect the weaknesses and problems that allow to determine the corrective actions to be taken, whether in terms of records, maintenance, supervision, security and patrimonial control in general.